Abnormal emotional processing in maltreated children diagnosed of Complex Posttraumatic Stress Disorder. (November 2017) - Bertó, Clara; Ferrin, Maite; Barberá, María; Livianos, Lorenzo; Rojo, Luis; García-Blanco, Ana
Abstract: Maltreated children usually show a specific pattern of emotional and behavioral symptoms that exceed those relating to posttraumatic stress disorder (PTSD). These symptoms have been defined as Complex PTSD (CPTSD). The underlying attentional mechanisms of abnormal emotional processing and their relation to the clinical presentation of CPTSD are not well understood. A visual dot-probe paradigm involving pre-attentive (i.e., 500 ms) and attentive (i.e., 1500 ms) presentation rates of neutral versus emotional (i.e., angry, happy or sad) facial expressions was applied. Twenty-one maltreated CPTSD children were compared with twenty-six controls. The results are as follows: an attention bias away from threatening faces and an attentional bias towards sad faces were observed in maltreated CPTSD children during pre-attentive and attentive processing. Whereas the attentional bias away from angry faces was associated with social problems, the attentional bias towards sad faces was associated with depressive and withdrawn symptoms. Therefore, CPTSD children develop maladaptive negative cognitive styles, which may underlie not only social problems (by a cognitive avoidance of threatening stimuli) but also depressive symptoms (by a cognitive approach to sad stimuli). Attention processing abnormalities should be considered as therapeutic targets for new treatment approaches in this population.